2008
DOI: 10.1002/syn.20548
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole and its human metabolite OPC14857 reduce, through a presynaptic mechanism, glutamate release in rat prefrontal cortex: Possible relevance to neuroprotective interventions in schizophrenia

Abstract: Aripiprazole is a novel atypical antipsychotic drug with neuroprotective properties. As excessive glutamate release is now considered to be part of the pathophysiology of schizophrenia, the objective of this study was to use an in vitro assay system to investigate the effect of aripiprazole and its human metabolite OPC14857 on the release of endogenous glutamate from isolated nerve terminals (synaptosomes), freshly prepared from rat prefrontal cortex. Both aripiprazole and OPC13857 potently inhibited 4-aminopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
1
18
1
Order By: Relevance
“…A pattern of effects in the 5-CSRTT similar to those seen here with aripiprazole was observed after intracortical injection of 8-OH-DPAT , which also suppressed the CPP-induced rise of extracellular GLU (Calcagno et al 2006). In addition, aripiprazole suppressed GLU release induced by the potassium channel blocker 4-aminopyridine in synaptosomes of the rat mPFC, and WAY100635 abolished this effect (Yang and Wang 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A pattern of effects in the 5-CSRTT similar to those seen here with aripiprazole was observed after intracortical injection of 8-OH-DPAT , which also suppressed the CPP-induced rise of extracellular GLU (Calcagno et al 2006). In addition, aripiprazole suppressed GLU release induced by the potassium channel blocker 4-aminopyridine in synaptosomes of the rat mPFC, and WAY100635 abolished this effect (Yang and Wang 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence for 5-HT 2A antagonist reduction of cocaine seeking (Filip 2005; Fletcher et al 2002), 5-HT 2A receptor occupancy by aripiprazole does not exceed 50%, even at doses as high as 30 mg/kg, while D 2 receptor occupancy shows an ED 50 of 0.7 mg/kg (Natesan et al 2006). It would be premature to rule out a role for other receptor targets of aripiprazole, however, as some of the effects of aripiprazole on DA may involve interactions with 5-HT 1A receptors (Bortolozzi et al 2007), as well as modulation of glutamate activity in the prefrontal cortex (Yang and Wang 2008), a pathway well implicated in relapse (Kalivas et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Another study has suggested that aripiprazole inhibits glutamate release from rat prefrontocortical nerve terminals, probably by the activation of dopamine D 2 and 5-HT 1A receptors, which subsequently results in the reduction in nerve terminal excitability and downstream activation of voltage-dependent Ca 2+ channels through a signaling cascade involving PKA. These actions of aripiprazole may contribute to its neuroprotective effect in excitotoxic injury [29] . In SH-SY5Y human neuroblastoma cells, aripiprazole increased the levels of brain-derived neurotrophic factor (BDNF)-mediated signaling, suggesting that aripiprazole offers neuroprotective effects on human neuronal cells [30] .…”
Section: Genotoxic Parametersmentioning
confidence: 99%